Rekayasa Desain dan Analisis Struktur perangkat dasar laut Ocean Bottom Unit (OBU) untuk INA – TEWS - Wibowo Harso Nugroho; Nanang J H Purnomo; Ogi Ivano; S Handoyo (Universitas Muhammadiyah Sidoarjo, 2016)
This paper briefly describes the design and analysis of the structure of ocean bottom units (OBU) as a pair of surface buoys to detect tsunami early. This engineering work such as any other marine construction is based on naval architecture. The design concept OBU is firstly made then the stability calculation is conducted, finally the structural strength is calculated for load case of hydrostatic and impact as the OBU landed on approximately 2000m of ocean depths.